2005
DOI: 10.1007/s00066-005-1416-5
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Sparing Treatment in Muscle-Invasive Bladder Cancer

Abstract: The data obtained in this study confirm the high efficacy of TUR and radiochemotherapy for locally advanced bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…The 5-year survival rate in that study was 45%. When comparing the results of these previous studies including more intensive chemoradiation programs mainly for the primary treatment of muscle-invasive bladder cancer to the results of our present series, the results of the present study with a 5-year survival rate of 100% can be considered quite promising (6,11). Since the current study included only a very small number of patients, its findings need to be confirmed in a larger prospective trial.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The 5-year survival rate in that study was 45%. When comparing the results of these previous studies including more intensive chemoradiation programs mainly for the primary treatment of muscle-invasive bladder cancer to the results of our present series, the results of the present study with a 5-year survival rate of 100% can be considered quite promising (6,11). Since the current study included only a very small number of patients, its findings need to be confirmed in a larger prospective trial.…”
Section: Discussionsupporting
confidence: 48%
“…In the previous study, 13 of 42 patients (31%) died, 7 patients (17%) due to bladder cancer (6) and 3 patients (7%) due to development of local recurrence. In another study of 68 patients receiving organpreserving treatment for primary muscle-invasive bladder cancer, 34 patients (50%) were treated with chemoradiation in vivo 31: 239-242 (2017) 240 (11). The 5-year survival rate in that study was 45%.…”
Section: Discussionmentioning
confidence: 92%
“…Generally, a total dose of 60 Gy or higher is used , with concurrent chemotherapy, and these combined chemotherapies yield high response rates. 5,7,12 Our initial radiotherapy consisted of a 40-Gy dose followed by a 20-Gy boost. However, the boost radiotherapy was difficult to complete due to the side-effects and the requirement for a longer hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…• Cisplatin, a drug with a known radiosensitizing effect on other types of organ tumors [2,5,8,18,19,31], was also added to the chemotherapy protocol for patients with locally advanced tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, certain drugs, in particular taxanes, were shown to be potent cytostatic agents for systemic treatment of breast cancer [1,23,29] as well as radiosensitizers for treatment of other tumor entities [8,18,19,31]. We have compiled the largest amount of data ever published regarding toxicity and efficacy with high-dose radiotherapy plus chemotherapy with a taxane alone (paclitaxel or docetaxel; TAX/RT) or in combination with cisplatin (paclitaxel plus cisplatin; TAX/CIS/RT) in recurrent breast cancer.…”
Section: Introductionmentioning
confidence: 99%